Michael Finnissy: piano quintet in B flat major (EG 118) (completion) - Grieg, Edvard 1843-1907; Finnissy, Michael 1946- (Oxford Oxford university press, 2013)
In this work, the only published completion of Grieg's Piano Quartet in B-flat, we hear how Finnissy takes Grieg's style and weaves it together with modern expression and references to Grieg's contemporaries Lindeman, Mendelssohn, and Wagner.